Brand Image, Price Perception and Product Quality Factors That Influence The Iphone Purchase Decision of STIE Tri Bhakti’s Students - Fitrasyah Nurmulya; Irene Yuniar (STIE Tri Bhakti, 2025)
The contradiction between students' financial capabilities and their purchasing decisions for premium products such as iPhones shows that there are strong psychological and perceptual factors. The purpose of this study is to determine the influence of brand image, price perception, and product quality on iPhone smartphone purchasing decisions among students at STIE Tri Bhakti Bekasi City. This study uses quantitative research methods. The sampling technique uses purposive sampling. The criteria for selecting respondents are those who have used and are active users of iPhone smartphones. This study is supported by SPSS software version 26 to obtain research results. The results of this study determine that 1. Brand image partially has a positive and significant effect on purchasing decisions; the t-value is 8.164. t-table 1.664, the significance level is 0.000 < 0.005, so hypothesis one is accepted. 2. Price perception partially has a positive and significant effect on purchasing decisions; the t-value is 3.214. t-table 1.664, the significance level is 0.002 < 0.005, so hypothesis two is accepted. 3. Product quality partially has a positive and significant effect on purchasing decisions; the calculated t value is 6.721 > t table 1.664, and the significant level is 0.000 < 0.005, so the third hypothesis is accepted. 4. Brand image, price perception, and product quality simultaneously have a positive and significant effect on purchasing decisions; the calculated f value is 134.855 > ft table 2.72, and the significant level is f 0.000 < 0.05, so the fourth hypothesis is accepted. The coefficient of determination (R²) has an R-square value of 0.829, or 82.9%, which means that the independent variables, namely brand image, price perception, and product quality, can explain purchasing decisions by 82.9%, while the remaining 17.1% is explained by other variables